Calculation of fermentation parameters from the results of a fed-batch test taking account of the volume of biomass in the fermenting medium - Borzani,Walter (2008)
The volume of biomass in the fermenting medium may significantly affect the values of fermentation parameters calculated from the measured concentrations of the substrates and/or products. The corrections proposed in this paper should be evaluated and, depending on their magnitude, considered in order to obtain more representative results. A numerical example is presented.